Autocrine/Paracrine Function of Globular Adiponectin: Inhibition of Lipid Metabolism and Inflammatory Response in 3T3‐L1 Adipocytes. Issue 5 (May 2015) - Lazra, Yulia; Falach, Alona; Frenkel, Lital; Rozenberg, Konstantin; Sampson, Sanford; Rosenzweig, Tovit
ABSTRACT Adiponectin is an adipose‐derived hormone, with beneficial effects on insulin sensitivity and inflammation. The aim of this study was to clarify the autocrine/paracrine effects of globular adiponectin (gAd) administrated during differentiation on the function of the mature adipocytes. Experiments were performed on 3T3‐L1 preadipocytes treated with gAd (10 nM), starting at an early stage of differentiation. gAd treatment during differentiation was without effect on mRNA expression of adiponectin and AdipoR2, but increased AdipoR1 expression. PPARgamma, perillipin and FABP4 mRNA expressions were lower in gAd‐treated adipocytes, accompanied by a reduction in lipid accumulation. While mRNA expression of HSL was not affected by gAd compared to untreated adipocytes, both ATGL and FAS were reduced, indicating that gAd regulates both lipolysis and lipogenesis. PPARα, ACOX2 and UCPs mRNA expressions were not affected by gAd, indicating that the reduction in lipid content is not attributed to an increase in fatty‐acid oxidation. In accord with the lower PPARγ expression, there was reduced Glut4 mRNA expression; however, insulin‐induced PKB phosphorylation was enhanced by gAd, and glucose uptake was not altered. To investigate the effect of gAd on LPS‐induced inflammatory response, cells were treated with gAd either during differentiation or 24 h before induction of inflammation in differentiated adipocytes. LPS‐induced inflammatory response, as indicated by increase in IL6 and MCP‐1 mRNA expression. gAd given through differentiation was much more effective in abrogating LPS‐dependent cytokines production than gAd given to the mature adipocyte. In conclusion, elevated gAd at differentiation of 3T3‐L1 cells leads to reduced lipid content, reduced lipid metabolism and high resistance to inflammation. J. Cell. Biochem. 116: 754–766, 2015. © 2014 Wiley Periodicals, Inc.